Site Specific Non-Linear Ground Response Analysis and Soil Structure Interaction Study of Newly Constructed Dharahara Tower - Katuwal, Santosh; Bijukchhen, Subeg Man; Kawan, Chandra Kiran; Shilpakar, Anjali (Journal of Science and Engineering, 2023)
This study investigates the seismic performance of the recently reconstructed Dharahara tower, a historically significant monument in Nepal that has experienced damage in past earthquakes and was completely destroyed in the recent Gorkha earthquake. Ground Response Analysis (GRA) and Soil-Structure Interaction (SSI) investigations are conducted to assess its structural behavior. GRA includes free field and structure-influenced analyses, with subsequent comparative assessment. Additionally, 3D non-linear finite element analysis is employed to derive equivalent spring constants representing soil and foundation characteristics, which are incorporated into the SSI analysis. These computed spring constants are used to model support conditions, allowing for an evaluation of the super-structural response. The study also employs non-linear dynamic analysis to compare structural responses between fix-based and spring-based models. The results indicate that the presence of the structure significantly influences surface wave motion amplification in GRA, resulting in peak ground accelerations (PGAs) that exhibit de-amplification in the free field and amplification in the presence of the structure. Furthermore, the introduction of an equivalent spring system in the soil-structure model changes the system's vibration period and damping characteristics, leading to enhanced dynamic response compared to the fixed-base model.